ФАКТОРИ ВПЛИВУ НА НАПРУГУ ДОТИКУ З ОГЛЯДУ РОЗРОБКИ РЕКОМЕНДАЦІЙ ДЛЯ РЕКОНСТРУКЦІЇ ЗАЗЕМЛЮВАЛЬНОГО ПРИСТ - Коліушко, Д.Г.; Руденко, С.С. (Інститут електродинаміки НАН України, Київ, 2019)
The purpose of the work is to determine the factors that affect the value of touch voltage during the synthesis of recommendations for reconstruction of the grounding while minimizing labor and material costs. The dependences of the touch voltage on the single-phase ground fault current, the soil electrophysical characteristics, the design of thegrounding, and the base resistance in the place, where equipment is serviced, are investigated. At the same time, statistical data of the energy objects, where measurements were carried out, tools for mathematical modeling of the electrical potential distribution in the grounding device and methods of physical experiment were used. In the paper thevalue of the saturation current for a fixed size of a uniform grounding grid is determined, taking into account the influence of all four types of three-layer soil on the touch voltage. The asymmetry of the touch voltage distribution along the equipment lines depending on the distance to the grounding edge is shown. According to results, the research directions have been formed to develop the unified methodology for the synthesis of recommendations for reconstruction of the grounding using the predictive model of the touch voltage assessment before calculations. References 15, figures 6, table 2.